Peningkatan Keterampilan Anggota Karang Taruna Melalui Pelatihan Pembuatan Website - Endah Wiji Lestari; Sri Hardani; Leliyanah Leliyanah; Hanafi Eko Darono (Universitas Muhammadiyah Palembang, 2025)
The development of the internet has been very rapid and its use covers various areas of life. This resulted in a drastic change in people's lives from previously being an offline society to becoming an online society. Internet users are also increasing from time to time. Like the development of the internet, the existence of websites as a form of technological improvement in internet use is also experiencing rapid development. Various forms of organizations use websites for various purposes. UKKT RW. 06 Tegal Parang Subdistrict is a youth organization which is a forum for fostering and developing the creativity of the young generation in the RW. 06 Tegal Parang Village. Like other organizations, UKKT RW. 06 Tegal Parang Subdistrict also needs a website to convey various information such as work programs, activities and other announcements to the wider community quickly and easily. Currently UKKT RW. 06 Tegal Parang Subdistrict does not yet have a website, so all information is still conveyed through leaflets handed out to residents or posted on notice boards. Providing website creation training to UKKT RW. 06 Tegal Parang Subdistrict not only provides solutions to website needs at UKKT RW. 06 Tegal Parang Subdistrict but also provides skills to UKKT RW members. 06 Tegal Parang Village which could be useful in the future. The training was carried out offline in the Tegal Parang Village Hall and was attended by UKKT RW administrators and members. 06 Tegal Parang Village. With this training, it is hoped that UKKT RW administrators and members will. 06 Tegal Parang Subdistrict have useful skills and are able to create and manage their own website. The results of this community service will be published through articles in electronic media and community service journals